2020
DOI: 10.1097/brs.0000000000003566
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Parameter Can Guide Concave Rod Contour for the Correction of Hypokyphosis in Adolescent Idiopathic Scoliosis

Abstract: Study Design. Retrospective. Objective. To evaluate the effect of preoperative rod shape on 3D spinal deformity correction. Summary of Background Data. Differential rod contouring is a surgeon-dependent process based on an estimate of 3D deformity correction sought and the flexibility of the spine. An objective measure to this otherwise subjective scoliosis correction technique is lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…of patients Gender Patient Characteristics Study groups (no. of patients) Type of surgery Mean age at surgery (years) Follow-up Mean (SD), months) Male ( n ) Female ( n ) Machino et al (2020) [ 25 ] Cohort study 67 8 59 AIS Posterior rods and pedicle screws PLIF 14.4 mean NR Kluck et al (2020) [ 26 ] Cohort study 99 NR NR AIS Posterior rods and pedicle screws NR 14 ± 2 years NR Shen et al (2020) [ 27 ] Cohort study 19 0 19 AIS Posterior rods and pedicle screws PLIF 15.6 ± 2.1 NR Miyazaki et al (2020) [ 28 ] Cohort study 27 NR NR AIS Hypokyphotic normal–hyperkyphotic PSF with double-rod rotation NR NR Feeley et al (2019) [ 29 ] Cohort study 31 8 23 AIS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of patients Gender Patient Characteristics Study groups (no. of patients) Type of surgery Mean age at surgery (years) Follow-up Mean (SD), months) Male ( n ) Female ( n ) Machino et al (2020) [ 25 ] Cohort study 67 8 59 AIS Posterior rods and pedicle screws PLIF 14.4 mean NR Kluck et al (2020) [ 26 ] Cohort study 99 NR NR AIS Posterior rods and pedicle screws NR 14 ± 2 years NR Shen et al (2020) [ 27 ] Cohort study 19 0 19 AIS Posterior rods and pedicle screws PLIF 15.6 ± 2.1 NR Miyazaki et al (2020) [ 28 ] Cohort study 27 NR NR AIS Hypokyphotic normal–hyperkyphotic PSF with double-rod rotation NR NR Feeley et al (2019) [ 29 ] Cohort study 31 8 23 AIS …”
Section: Resultsmentioning
confidence: 99%
“…The pooled MD in change in kyphosis angle with 6 mm rods was 13.69° (95% CI: 8.54°–18.84°). Similarly, three eligible studies utilizing 5.5 mm rods reported corresponding change in kyphosis angle were also analyzed [ 26 , 52 , 67 ]. Our analysis revealed a pooled MD of 10.05° (95% CI 8.53°–11.57°) in kyphosis angle.…”
Section: Resultsmentioning
confidence: 99%
“…The average hospital stay for our patients was 5.38 days, which was comparable to the average stay in other studies. In our cohort, we used dual differential rod contouring (DRC) in all cases, with the concave rail being over-contoured by 20 degrees [ 11 , 14 , 43 , 44 ]. This technique represents an additional correction strategy involving over-contouring of the concave rail to pull the concave side of the curve posteriorly, and under-contouring of the convex rod to push the convex side of the curve anteriorly and achieve a simultaneous correction in three planes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo and biomechanical studies have demonstrated the efficacy of DRC in achieving 3D deformity correction and have demonstrated the association of increased over-correction of the concave rod with increased amounts of sagittal plane correction and the ability to achieve correction in both the instrumented thoracic spine and in the un-instrumented lumbar spine [ 14 , 18 , 43 ]. Kluck et al commented that [ 44 ] differential rod contouring in DRC is, by nature, subjective. Concave and convex rod contours are determined intraoperatively by the treating surgeon based on estimates of the desired sagittal profile and severity of the axial plane rotation.…”
Section: Discussionmentioning
confidence: 99%
“…This effectively pulls the concave side of the curve to an overcontoured rod while pushing down on the convex side of the curve with an undercontoured rod. 33-37,40…”
Section: Surgical Considerations To Optimize Restoration Of Thoracic ...mentioning
confidence: 99%